Mutual fund's trading and Chinese mergers and acquisitions - Bi, Xiao Gang; Wang, Danni (Elsevier, 2014)
In developing capital markets dominated by individual investors, there is a potential for greater disparity in the interests of institutional investors and controlling shareholders and this has implications for the trading and monitoring activities of institutional investors in these markets, particularly around high impact corporate decisions. We examine the trading activities of mutual funds (as the largest institutional investor in this market) in corporate acquisition activities where there is potential for a wide disparity of interest between institutional investors and controlling shareholders. We find that Top Mutual Fund Management Company (TFC) have strong incentives to trade and realize profits over the event months for fear of price drop due to the mean reversion and herding effect in Chinese capital market.